Morphological and cytogenetic characterization of four canna (Canna x generalis L.H. Bailey and E.Z. Bailey) cultivars and two putative F1 hybrids - Ondoy, Juareyn L.; Mendioro, Merlyn S.; Magdalita, Pablito M.; Dela Viña, Celia B.; Reamillo, Maria Cecilia S. (2020)
Four Canna cultivars (C. 'Moonbeam', C. 'Madeira,' C. 'Wintzer's Colossal', C. 'Alphonse Bouvier') and two putative F1 hybrids of C. 'Wintzer's Colossal' and C. 'Alphonse Bouvier' (coded as H3R1 and H3R2, respectively) were evaluated for their morphological and cytogenetic characteristics. Among the morphological parameters reckoned were plant height, culm/stem diameter, flower diameter, flower color, inflorescence length, staminode length and thickness, leaf length, leaf width and leaf thickness. Acetocarmine squash technique was used to determine the chromosome number and chromosome behavior at meiosis I and II. Pollen viability was tested using I2KI test and TTZ test which was further verified through pollen germination test. Meiotic behavior was related to pollen fertility. Results showed that the four Canna cultivars and two putative F1 hybrids were morphologically variable in plant height, inflorescence length flower diameter and staminode length with measurements of 95.67 – 172.67 cm, 22.33 – 147.67 cm, 6.33 – 11.94 cm, and 9.95 – 45.87 cm, respectively. The flower color of C. 'Moonbeam' is Chartreuse yellow, C. 'Madeira' is Saturn red, and C. 'Alphonse Bouvier' is Vermillion while C. 'Wintzer's Colossal' is Nasturtium red. The color of the two putative F1 hybrids is Chartreuse yellow for H3R1 and Jasper red for H3R2. C.'Moonbeam', C.'Madeira' and the two putative F1 hybrids are diploid with chromosome number 2n = 18, and basic chromosome number x = 9. Although non-congressions and laggards were observed at metaphase I and anaphase I, the chromosome were able to catch up, hence pollen stainability and pollen germination remained high at 90.36% to 94.88% Pollen viability for H3R2 were 95.75% and 90.38%, respectively. C.'Witzer's Colossal' is a triploid with gametic chromosome number of 3n = 27, and a high frequency of irregular chromosome behavior observed during meiosis I and II. It has low pollen stainability based on results of the I2KI test while unstained pollen was observed based on the TTZ test result. C.'Moonbeam' and C.'Madeira' can be used as a female parent as well as a male parent due to their high pollen viability. The two putative F1 hybrids H3R1 and H3R3 had a novel staminode size and attractive colors that ornamental breeders and Canna enthusiasts may find valuable.
Keywords: Canna; Hybridization